REPUBLICAN PRINCIPLE AND THE RESPONSIBILITY OF SOCIAL NETWORK PROVIDERS: IMPACTS ON SOCIAL BEHAVIOR (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present work intends to address the responsibility of social network providers in light of the republican principle, also analyzing the current decisions on the subject in the Superior Courts. With the increasing use of social networks, there is a significant impact, both on Law and on life in society. Freedom of expression, a fundamental right guaranteed by the Federal Constitution (article 5, item IV) and by Law 12,965/2014 (article 2), allows individuals to use the internet to express their opinions and expose their activities, in general. However, the indiscriminate use of these platforms also facilitates the commission of crimes without major consequences for offenders, which raises concerns not only for the Law, but also regarding good coexistence, equality and the structure of the State. Using the dialectical method, the work revisits philosophical thoughts and the General Theory of the State, applying them to the field of civil liability of social network providers in contemporary times. Jurisprudential research shows that fundamental rights must be preserved, in light of the republican principle, balancing them with human rights and social values, guaranteeing coexistence based on respect, justice and responsibility.